Risk factors associated with hemoglobin levels and nutritional status among Brazilian children attending daycare centers in Sao Paulo city, Brazil - de Novaes Oliveira, Mariana; Martorell, Reynaldo; Nguyen, Phuong (Archivos Latinoamericanos de Nutrición (ALAN), 2021)
Like many other developing countries, Brazil has been going a nutritional transition which presence both malnutrition and overweight. Stunting and overweight are the major public health problems in Brazilian children. The objective of this study was to document the prevalence of stunting, overweight and anemia in preschool children and examine if those nutritional problems are related; also identify if these nutritional problems have the same risk factors. Data from the “Efficient Daycare Center Project” which include 270 children attending nurseries of eight daycare centers in Sao Paulo city, Brazil were used for this study. Data on height and weight were converted to z-scores using WHO anthro software. Hemoglobin (Hb) concentrations were determined on finger-prick blood samples. The co-occurrence of stunting, overweight and anemia was investigated by contingency tables a log-linear model. Univariate and multiple regression analyses were performed to estimate the association of HAZ, WAZ, WHZ and Hb levels with their risk factors. The results showed high prevalence of overweight (22.2%), risk of stunting (22.6%) and anemia (37%). Percent of daycare attendance, age, number of siblings under 5 years old and per capita income are associated with Hb levels. This study provides evidence that Brazil is going through a nutritional transition and suggest that the adoption of public policies to expand and improve services in daycare centers may help to prevent multi-nutritional problems in preschool children. Como muchos otros países en desenvolvimiento Brasil esta pasando por la transición nutricional, la cual tiene presente a la desnutrición y sobrepeso. Este estudio tuvo como objetivo mostrar la prevalencia de baja estatura, sobrepeso y anemia en niños en edad preescolar y analizar si esos problemas nutricionales están relacionados; también identificar si esos problemas nutricionales presentan los mismos factores de riesgo. Fueron utilizados datos del “Proyecto CrechEficiente” el cual estudio 270 niños que asisten a cunas de ocho jardines de la infancia en la ciudad de Sao Paulo, Brasil. Los datos de peso y estatura fueron convertidos en z-escore utilizando el software WHO Anthro. La extracción de sangre para la determinación de hemoglobina (Hb) se realizó por punción digital. La co-ocurrencia de baja estatura, sobrepeso y anemia fue investigada a tráves de tablas de contingencia y modelo loglinear. Fueron realizados análisis univariados y regresión múltiple para determinar la asociación entre TEZ, PEZ, PTZ y niveles de hemoglobina con sus factores de riesgo. Los resultados mostraran elevada prevalencia de sobrepeso (22,2%), riesgo para baja estatura (22,6%) y anemia (37%). El porcentaje de frecuencia a los jardines infantiles, edad, número de hermanos menores de 5 años y renta per cápita están asociados con los niveles de hemoglobina. Este estudio muestra evidencia de que el Brasil esta pasando por una transición nutricional y sugiere adopción de políticas públicas para difundir y mejorar los servicios de los jardines infantiles pudiendo ayudar a prevenir varios problemas nutricionales en niños en edad preescolar.